2005
DOI: 10.1080/18811248.2005.9726374
|View full text |Cite
|
Sign up to set email alerts
|

Subcriticality Measurement of Pressurized Water Reactors during Criticality Approach using a Digital Reactivity Meter

Abstract: A mockup experiment of subcriticality measurement with a digital reactivity meter during criticality approach in a PWR was carried out using plant data. There are some difficulties in the direct application of a digital reactivity meter to the subcriticality measurement. Some treatments were needed in using the count rate of Source Range (SR) detector as input signal to the digital reactivity meter. To overcome these difficulties, we proposed a digital reactivity meter combined with a methodology of the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…2,3,4,5 It was necessary to correct all results of the experiments 6 for the temperature of 20.5°C, to be possible make the comparison with the theoretical results. The theoretical analysis was performed by the reactor physics code MCNP-5, using the nuclear data library ENDF/B-VII.0.…”
Section: Methodsmentioning
confidence: 99%
“…2,3,4,5 It was necessary to correct all results of the experiments 6 for the temperature of 20.5°C, to be possible make the comparison with the theoretical results. The theoretical analysis was performed by the reactor physics code MCNP-5, using the nuclear data library ENDF/B-VII.0.…”
Section: Methodsmentioning
confidence: 99%
“…2,3,4,5 It was necessary to correct all results of the experiments for the temperature of 20.5°C, to be possible make the comparison with the theoretical results. The theoretical analysis was performed by the reactor physics code MCNP-5, using the nuclear data library ENDF/B-VII.0.…”
Section: Methodsmentioning
confidence: 99%
“…In the foregoing study, 1) we have simulated criticality approach calculation by a digital reactivity meter using the initial reference subcriticality in which contains various errors. The estimated subcriticalities were found that they have good accuracy with the true value when the initial subcriticality was exact.…”
Section: Initial Reference Subcriticality and Error Contributionmentioning
confidence: 99%
“…It has been shown that a digital reactivity meter could monitor subcriticality continuously during criticality approach in a PWR. 1) However there still exist some technical issues to be investigated. One of them is that of sampling interval of the neutron signal to be used for the reactivity calculation by a digital reactivity meter.…”
Section: Introductionmentioning
confidence: 99%